2020
DOI: 10.3390/universe6050063
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Electrical Conductivity and Magnetization Parameter of Neutron Star Crusts and Applied to the High-Braking-Index Pulsar PSR J1640-4631

Abstract: Young pulsars are thought to be highly magnetized neutron stars (NSs). The crustal magnetic field of a NS usually decays at different timescales in the forms of Hall drift and Ohmic dissipation. The magnetization parameter ω B τ is defined as the ratio of the Ohmic timescale τ O h m to the Hall drift timescale τ H a l l . During the first several million years, the inner temperature of the newly born neutron star cools from T = 10 9 K to T = 1.0 × 10 8 K, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 48 publications
(77 reference statements)
0
22
0
Order By: Relevance
“…The magnetization parameter, ω B τ , is defined as the ratio of the ohmic timescale τ Ohm to the Hall drift timescale τ Hall , where ω B is the electron gyrofrequency, and τ is the electron relaxation time. We calculated the crust conductivity of NSs and gave a general expression of ω B τ ωBτ150B0/1013G, for young pulsars (Wang et al 2020). It was found that, when B ≤ 10 15 G, the conductivity increases slightly with the increase in the magnetic field strength B due to the quantum effects, the enhanced B has a small effect on the matter in the low‐density regions of the crust and has almost no influence on the matter in the high‐density regions.…”
Section: Toroidal Magnetic Field Dissipationmentioning
confidence: 99%
“…The magnetization parameter, ω B τ , is defined as the ratio of the ohmic timescale τ Ohm to the Hall drift timescale τ Hall , where ω B is the electron gyrofrequency, and τ is the electron relaxation time. We calculated the crust conductivity of NSs and gave a general expression of ω B τ ωBτ150B0/1013G, for young pulsars (Wang et al 2020). It was found that, when B ≤ 10 15 G, the conductivity increases slightly with the increase in the magnetic field strength B due to the quantum effects, the enhanced B has a small effect on the matter in the low‐density regions of the crust and has almost no influence on the matter in the high‐density regions.…”
Section: Toroidal Magnetic Field Dissipationmentioning
confidence: 99%
“…Dong et al (2014)) found that both “outliers” of BH XRBs and bright AGNs follow a steeper fundamental plane of black hole activity. Coriat et al (2011) argued that the two fundamental planes are regulated by radiatively inefficient (e.g., ADAF) and radiatively efficient accretion processes (e.g., SSD + corona), respectively, if we assume the jet launching and radio radiation behave identically (see also, Deng et al 2020; Gao et al 2011a; Fu et al 2020; Li et al 2016; Zhu et al 2016; Wang et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have adopted unified equations of state for cold non‐accreting neutron stars with the Hartree‐Fock‐Bogoliubov method, developed by Pearson et al (2018), and choose two fiducial dipole magnetic fields of B = 1.0 × 10 13 G and B = 1.0 × 10 14 G, four different temperatures, T , and two different impurity concentration parameters, Q , and then calculated the conductivity of the inner crust of NSs and gave a general expression of magnetization parameter for young pulsars ωBτ150B0/1013G, by using numerical simulations, where ω B is the electron gyro‐frequency, and τ is the electron relaxation time (Wang et al 2020, Gao et al 2021). It was found that when B ≤ 10 15 G, the conductivity increases slightly with the increase in the magnetic field strength due to the quantum effects, the enhanced magnetic field strength has a small effect on the matter in the lowdensity regions of the crust, and almost has no influence on the matter in the highdensity regions.…”
Section: Magnetization Parameter Thermal Conductivity and Thermal Ementioning
confidence: 99%
“…The effect of Hall drift depends on the initial field strength and structure and how fast the NS cools. During the Hall drift stage, the toroidal field is strongly rearranged and dissipated, after this stage, the long‐term evolution seems to select, generally, a predominantly quadrupolar/octupolar structure concentrated in the inner crust and which tends to be stronger close to the poles (Deng et al 2020; Fu et al 2020; Gao et al 2017a, 2017b, 2017c, 2019a, 2019b; Li et al 2016; Wang et al 2020).…”
Section: Introductionmentioning
confidence: 99%